Evaluation of Cell Biomarker Gene Expression (CD34) in ALL Patients and Healthy Controls Expression (CD34) in People with Leukemia - goolshan moradozadeh; noosha zia jahromi; hosein sazgar (Journal of Advanced Biomedical Sciences, 2020)
Background & Objective: CD34 is a prognostic factor in determining the prognosis of patients with acute myeloid leukemia. Since the relationship between expression of the marker of the CD34 cell line and many cancers has been proven today, in this study, the measurement of the expression of this marker with leukemia was investigated. Materials & methods: The present study is a case-control study performed on 30 healthy blood samples and 30 blood samples from blood donors. Lymphocytes were isolated using Ficole method. RNA was extracted. After synthesis of cDNA, expression regions were determined using Real Time RT-PCR with an internal control of GAPDH. Results: After performing the PCR reaction with specific primers in Real Time RT PCR and analyzing the results, the expression of CD34 gene in the blood of cancer patients was increased compared to healthy subjects (F = 21.588, P-Val = 0.002). Conclusion: Finding new biomarkers, which are a common indicator of cancer, can help with early diagnosis and recovery during cancerous illnesses. By reviewing these biomarkers, it is possible to develop new anti-cancer drugs that can target cancerous cells and prevent growth from growing into cancerous cells.